Novelties and Expected Impact From Changes in the Macedonian Social Protection Legislation - Bornarova, Suzana; Bogoevska, Natasha (Institute for Political Studies, 2022)
The new Law on Social Protection (LSP in further text) in the Republic of North Macedonia was adopted in 2019 as part of a social reform process in line with the key strategic goals within the social protection system. The main aspects of the new regulation focus on types, procedures and realization of social protection activities, the system, organization and institutional framework of social protection, as well as cadres, financing and oversight and other issues of importance for realization of social protection. The new LSP introduced many systemic changes which are reasonably interlinked in the text and provide for unhindered accomplishment of the key ongoing processes in social protection, such as deinstitutionalization, decentralization and pluralization in social services delivery. This article aims to identify impact and challenges related to implementation of the new social legislation, with focus on delivery and financing of social services. The content of this paper is a result of an analysis conducted in 2021 based on qualitative methodological approach and application of techniques of content analysis of relevant laws, bylaws, statistical data, reports, as well as expert interviews with representatives from relevant institutions – Ministry of Labour and Social Policy, Institute for Social Activities and representatives from national social service providers (public and private).